Mensagens dos tambores no morro: significados musicais, educação e projeto social pelo Grupo Arautos do Gueto - Rubens de Oliveira Aredes (2013)
This research aimed at an ethnomusicological analysis of the artistic and sociopedagogical work of Group Arautos do Gueto, headquartered in Morro das Pedras, slum of the western region of Belo Horizonte. The study was conducted through an ethnography, with special attention given to the construction of meanings in musical practice and teaching process. The analysis of musical meaning were developed videotaped interviews, conversations with group members, record in the study ofobservations and transcription of music to music transcription. The group exists since 1996, and consists of members of the community. It develops work with music and social project, aiming beyond artistic production, mechanisms around the practice of music that helps combat the influence of drug trafficking on children and adolescents the community. Not only the artistic production, but also their music is made on the practice of african-Brazilian percussion group. Their social work is based on their own theoretical elaborations, about the reality they live in and the effectiveness of their social work, built on the basis of their experiences of success and failure throughout itsyears of existence. The diversity of the sounds colours and heights of their drums, the diversity of nuances of patterns in the drums, the complex polyrhythms, all establish a rich layer of meaning in interaction together with the construction of a multifaceted identity of black urban, dweller of from the periphery; the environment characterized by the action of the drug trafficking and violence; the intention of transforming of reality lived in the slumsthrough social action, and the specific context of each musical performance. The analysis of musical meaning were based on their actual experiences, expectations, and elaborations, supporting me and on a theoretical framework built from the theoretical elaborations of Lucy Green about musical meaning and that of Lukács about ideology.